(2906) Proposal to reject the nameSalsola coquimbana(Chenopodiaceae/Amaranthaceae) - Jocou, Adriel I. (2022)
To avoid a disadvantageous change of names and future redun-dant nomenclatural discussions, we here propose the rejection of thenameSalsola coquimbanain accordance with Art. 56 of theICN(Turland & al. in Regnum Veg. 159. 2018). Acceptance of this pro-posal would neutralise the threat posed bySalsola coquimbanatothe well-established and unequivocal nameSalicornia neeiand itsderivatives, and avoid negative nomenclatural changes. Rejection ofthis proposal would mean thatSalsola coquimbana, an uncertainand forgotten name, could replaceSalicornia neei, a widely usedname for a South American species.